Вплив психічного статусу на імунологічні показники ротової рідини пацієнтів iз запальними захворюваннями пародонту - Дурягіна, Л.Х. (Таврический медико-биологический вестник, 2012)
Воспалительные заболевания пародонта широко распростанены в нашей стране. Мало изучены корреляционные связи психического состяния и иммунологических показателей ротовой жидкости у больных пародонтом. Мы изучили эти связи. The inflammatory diseases of paradontium are common in our country. Correlations between mental condition sand immunological indices of the mouth liquid in patients with diseases of parodontium have not been under thorough investigation.The present work is a study of these correlations.